2009
DOI: 10.1007/s00018-009-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

Display of proteins on Bacillus subtilis endospores

Abstract: The targeting and anchoring of heterologous proteins and peptides to the outer surface of bacteriophages and cells is becoming increasingly important, and has been employed as a tool for fundamental and applied research in microbiology, molecular biology, vaccinology, and biotechnology. Less known are endospores or spores produced by some Gram-positive species. Spores of Bacillus subtilis are surrounded by a spore coat on their outside, and a few proteins have been identified being located on the outside layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 107 publications
0
43
0
Order By: Relevance
“…The identification of spore surface proteins is becoming increasingly important for potential practical applications (9). It was proposed previously that CotA, CotB, CotC, and CotG are externally exposed on the surface of spores (6,8,15,25), whereas CotA-GFP, CotB-GFP, and CotC-GFP were not efficiently exposed on spores in this study (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The identification of spore surface proteins is becoming increasingly important for potential practical applications (9). It was proposed previously that CotA, CotB, CotC, and CotG are externally exposed on the surface of spores (6,8,15,25), whereas CotA-GFP, CotB-GFP, and CotC-GFP were not efficiently exposed on spores in this study (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Using a similar method, McKenney and coworkers also identified an outermost spore layer composed of CotG, CotW, and CotZ and demonstrated that this layer, which they termed the spore crust, is absent in cotXYZ mutant spores (16). The identification of spore surface proteins is also becoming increasingly important for potential practical applications (9). In this study, we demonstrate that the spore crust is the externally exposed, outermost component of the B. subtilis spore, forming a layer that covers the spore coat.…”
mentioning
confidence: 99%
“…Successful display of functional enzymes to the microbial cell surface shows increasing promise in developing whole-cell biocatalysts, as our society progresses toward an industrialized and technologically dependent future (60). However, the major challenge of a microbial surface display at the moment is the development of a system that is sufficiently robust for industrial applications (4,32,37,48). Fragility of the outer membrane of Gram-negative bacteria (e.g., E. coli) can be a major concern for surface display.…”
Section: Characterization Of Yhcr By Oussenko and Coworkersmentioning
confidence: 99%
“…Surface display, a powerful technique that uses different microbial components to express heterologous peptides or proteins, can effectively display the bioactive molecules on the surfaces of cells (16,32). Target proteins anchored on the outside of cells play a role in biocatalysis without the need for any purification or permeation procedure.…”
mentioning
confidence: 99%